Flow Study on Medium Size Pipeline Testing Loop - Tan Ni, King (2013)
In this research, a pipeline testing loop was constructed to study on the multiphase flow behavior in pipes. A fully design of equipments and piping network were constructed in this study by using Plant Design Management System (PDMS) software. The multiphase flow study was done by Computational Fluid Dynamic (CFD) software to identify the type of flow trends for different gasoil-vapour flow rate, gasoil-liquid flow rate, and water flow rate in a 6 inches diameter of pipe. The main purpose of this study was to perform the analysis of multiphase flow in order to understand the flow problem that is always encountered in the industry when transporting a mixture from reservoirs to the onshore oil production process. By working on the model fabricated on the pipeline testing loop, the multiphase flow study was able to be studied at the test section in the testing loop. The pipeline testing loop was created by constructing each of the equipments places in the pipeline such as tank, heat exchanger, and pump. The piping network was connected to all the equipments with valves and flanges. The multiphase simulation was carried out by six (6) different gasoil-vapour flow rates and four (4) different gasoil-liquid and water flow rates. Volume of Fluid (VOF) model was selected as the simulation approach to solve the surface tracking simulation.